2014
DOI: 10.1155/2014/892625
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Replacement with a Mechanical Valve for Severe Mitral Regurgitation in a Small Dog

Abstract: A seven-year-old Shih Tzu with refractory repeated pulmonary edema and syncope was presented for surgical operation. From the results of cardiovascular examinations, the dog was diagnosed as severe mitral regurgitation (ACVIM consensus class D) and mild tricuspid regurgitation. The dog first underwent surgery with mitral valve plasty; however, the results were unsatisfactory due to severe damage of the whole mitral valve. The operation was quickly changed to mitral valve replacement using a mechanical valve (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…We previously performed MVR in a small dog with severe, complicated MR (as in the dog in case 2) that died from thrombosis 2 years and 1 month after the operation. 25 It appears that MVP consisting of CR with ePTFE sutures and semicircular suture AP with Proline sutures improves the long-term durability and usability of repaired valves compared with replaced valves in small dogs. …”
Section: Discussionmentioning
confidence: 96%
“…We previously performed MVR in a small dog with severe, complicated MR (as in the dog in case 2) that died from thrombosis 2 years and 1 month after the operation. 25 It appears that MVP consisting of CR with ePTFE sutures and semicircular suture AP with Proline sutures improves the long-term durability and usability of repaired valves compared with replaced valves in small dogs. …”
Section: Discussionmentioning
confidence: 96%
“…Additionally, the cardioplegic solution volume was decreased to half of the usual volume (20 ml/kg) to avoid more hemodilution, although we used the lowest deep HT (ET 20°C) for cardioplegia. Thereafter, we used a hemoconcentrator to prevent excess hemodilution due to additional cardioplegic solution ( Taguchi et al ., 2014 ; Mihara et al ., 2017 ; Yokoyama et al ., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been increased reports of using MVP to treat MR in dogs (Kanemoto et al, 1990(Kanemoto et al, , 2004Boggs et al, 1996;Griffiths et al, 2004;Uechi, 2012). However, there have been few reports of the application of MVP to treat severe MR involving the posterior leaflet (PL) in small dogs (Boggs et al, 1996;Uechi, 2012;Kanemoto et al, 2017), in whom MVR was previously indicated (Orton et al, 2005;Taguchi et al, 2014). Herein, we describe a case of severe MR caused by multiple lesions in the PL in a mixed Chihuahua, who was treated with a combination of the following three MVP techniques: artificial chordal reconstruction (CR) for the anterior leaflet (AL) and the PL, semicircular suture annuloplasty (AP) for a dilated mitral annulus, and valvuloplasty (VP) using newly devised direct scallop sutures for the PL.…”
Section: Introductionmentioning
confidence: 99%